2015
DOI: 10.1016/j.amjsurg.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Early hospital readmission for gastrointestinal-related complications predicts long-term mortality after pancreatectomy

Abstract: BACKGROUND The purpose of this study was to investigate the prognostic significance of early (30-day) hospital readmission (EHR) on mortality after pancreatectomy. METHODS Using a prospectively collected institutional database linked with a statewide dataset, we evaluated the association between EHR and overall mortality in all patients undergoing pancreatectomy at our tertiary institution (2005 to 2010). RESULTS Of 595 pancreatectomy patients, EHR occurred in 21.5%. Overall mortality was 29.4% (median fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…[22][23][24] Although postoperative complications were not included in our definition of optimal surgery, hospital length of stay ≤7 days and absence of 30-day readmission serve as surrogates markers for complications that often drive lengthy hospitalizations and readmissions. 25,26 Lastly, patients in the optimal cohort appropriately received systemic chemotherapy, which aligns with current National Comprehensive Cancer Network guidelines. 27 Systemic therapy improves disease-free and overall survival for pancreatic cancer patients, and adherence to cancer care guidelines is therefore crucial for optimizing outcomes.…”
Section: Discussionmentioning
confidence: 79%
“…[22][23][24] Although postoperative complications were not included in our definition of optimal surgery, hospital length of stay ≤7 days and absence of 30-day readmission serve as surrogates markers for complications that often drive lengthy hospitalizations and readmissions. 25,26 Lastly, patients in the optimal cohort appropriately received systemic chemotherapy, which aligns with current National Comprehensive Cancer Network guidelines. 27 Systemic therapy improves disease-free and overall survival for pancreatic cancer patients, and adherence to cancer care guidelines is therefore crucial for optimizing outcomes.…”
Section: Discussionmentioning
confidence: 79%
“…Though this parameter has not been considered in majority of the studies, some authors have found it to be significant. 11,18 This is probably due to the fact that hypoproteinemia predisposes patients to increased risk of infections because of poor immunity. Moreover, hypoproteinemia leads to poor wound healing thus causing increased risk of anastomotic leak as well as wound dehiscence.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of ERAS against the risk of readmission remains unclear in patients undergoing PD, especially with its high risk of morbidity because full postoperative recovery compared to other gastrointestinal surgeries is known to take longer [12]. Unintended readmission after PD, that is reported to increase hospital cost for patients as well as morbidity and mortality, is considered to be a quality metric for surgery [13]. Therefore, it is important to evaluate the association between ERAS and readmission and to identify the risk factors for the same.…”
Section: Introductionmentioning
confidence: 99%